THE ROLE OF THE MAGISTRATE IN EXTRADITION PROCEEDINGS IN SOUTH AFRICA: MEANING OF “FAIR TRIAL” AND “COMPETENT COURT” IN A REQUESTING STATE - Jamil Ddamulira Mujuzi (Obiter, 2022)
The Extradition Act provides for two general modes of extradition: extradition to foreign states and extradition to associated states. In both cases, a magistrate has to issue a warrant of arrest for the person-to-be-extradited to be brought before him or her to conduct an enquiry to determine whether the person should be extradited. In the case of extradition to foreign states, the Minister responsible for justice has the final say on whether a person should be extradited. The magistrate’s role stops at authorising the detention of the person for the purposes of extradition. However, in the case of extradition to associated states, the magistrate has the final say on whether the person should be surrendered for extradition. In both cases, the magistrate plays a role – he or she has to issue a warrant for the arrest of the person in question. He or she also has to conduct an enquiry. The Constitutional Court held that before issuing a warrant of arrest, the magistrate must be satisfied that the person sought to be extradited has been convicted by a competent court. However, the Constitutional Court does not define or describe a “competent court”. The Constitutional Court also held that a person may not be extradited if his or her trial was unfair. However, it does not stipulate the yardstick that should be used to measure the fairness of the trial in a foreign or associated state. In this article, the author relies on international human rights law and on jurisprudence from South African courts to explain the meaning of “competent court”. The author also relies on international human rights law and jurisprudence from different countries to suggest the criteria that could be adopted by the Constitutional Court to determine whether a trial in a foreign or associated state was fair.